Strengthening of sentinel surveillance through priority settings in public health resource allocation - Gumashta, Raghvendra (International Journal Of Community Medicine And Public Health, 2017)
Background: Sentinel Surveillance assists in designing, re-designing and formulating health policy, programs and public health interventions and hence there is need to have a relook into the need for improving its implementation, monitoring and evaluation. Methods: Informal interview based cross sectional study was undertaken during January 2015 to December 2016 among the programmatic stakeholders including the doctors, laboratory technicians and support staff for understanding of the constraints observed during conduct of surveillance. Results: Time constraint and delayed supply of goods (94%), non-observance of guidelines (56%), dilution of sample quality (46%), requirement of training needs assessment (32%), absence of local communication network among stakeholders (68%), need for new initiatives (68%) and need for well trained staff during sample transport (34%) are important areas for quality enhancement. Conclusions: Framework support for surveillance requires strengthening from technical inputs of stakeholders thereby facilitating multi stage corrective actions directed towards achievement of appropriate public health actions.